Dietary compliance, dietary supplementation and traditional remedy usage of type 2 diabetic patients with and without cardiovascular disease - Tan, Mun Chieng; Ng, Ooi Chuan; Wong, Teck Wee; Anthony, Joseph; Abdul Rahman, Hejar; Abdul Aziz, Rushdan (Korean Society of Clinical Nutrition, 2015)
This analytical cross-sectional study examined the nutrient intakes, dietary compliance, dietary supplementation and traditional remedy usage in type 2 diabetes mellitus (T2DM) patients from selected tertiary hospitals in multi-racial Malaysia. We compared the different characteristics of T2DM patients with and without cardiovascular disease (CVD). Socio-demographic status, dietary intakes, dietary supplementation, traditional remedy use, medical history, anthropometric measurements and clinical characteristics were obtained from face-to-face interviews. A total of 313 patients who were treated for T2DM participated in this study, in which 36.1% of them had CVD. The mean age of study subjects was 55.7 ± 9.2 years; mean diabetes duration was 10.1 ± 8.1 years; 52.1% were females; and 47.0% were Malays. The mean total energy intake of the subjects was 1674 ± 694 kcal/day, and patients with CVD consumed higher total calories (p = 0.001). Likewise, the mean carbohydrate, protein and total fat intake of CVD patients were significantly higher than non-CVD patients (p < 0.05), while mean intakes of cholesterol, fibre, minerals and all vitamins were comparable between CVD and non-CVD patients. Regardless of CVD status, a notably high proportion of the subjects did not meet the recommendations of the Medical Nutrition Therapy Guidelines for Type 2 Diabetes for total energy, carbohydrate, protein, total fat, and fibre intakes. Meanwhile, 52.4% used at least one dietary supplement and 12.1% took single traditional remedy or in various combinations. Traditional remedies and supplement intake did not differ between CVD and non-CVD subjects. It is suggested that T2DM patients should be educated based on their personalized dietary intake, dietary supplementation and traditional remedy usage. The recommendations for T2DM patients shall be met to achieve the optimal metabolic goals and minimize the potential diabetic complications.